(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Information security models are structures of various algorithms and technologies that are of great importance in the field of cyber security. These models, including modern technologies such as Machine Learning (ML) and Artificial Intelligence (AI), are widely used in solving information security problems. There are also statistical models, encryption algorithms, and mathematical models that can be used to analyze and prevent information security problems. This annotation provides an overview of the types of information security models and their main important features.